A Novel Spectral-Efficient Coherent Radio-Over-Fiber Link With Linear Digital-Phase Demodulation - Huixing Zhang; Aijun Wen; Wu Zhang; Weipeng Zhang; Weile Zhai; Zhaoyang Tu (IEEE Photonics Journal)
In this paper, a novel spectral-efficient coherent radio-over-fiber (RoF) link with linear digital phase demodulation is proposed and experimentally demonstrated. At the transmitter, to make an efficient use of the optical power and spectra, an intensity-modulated optical signal serving as the optical reference signal and a phase-modulated optical signal are polarization-multiplexed on a single optical carrier. At the receiver, the two optical signals are coherently detected with an optical local oscillator (OLO) and demodulated free of laser phase fluctuation through digital signal processing. Owing to simple and linear digital phase demodulation, an RF input signal is linearly demodulated from the optical phase without approximations and preconditions, which preserves the linearity of the phase-modulated RoF optical link from the transmitter end to the receiver end. The proposed scheme is experimentally verified by 25-km single-mode-fiber (SMF) transmission of two 16-QAM microwave vector signals at 2 GHz and 2.4 GHz, both with a symbol rate of 50 Msymbol/s. The transmission performance in term of error vector magnitude (EVM) is evaluated. Additionally, 25-km SMF transmission of the phase-modulated input signal with a spurious-free dynamic range (SFDR) of 112.8 dB·Hz2/3 is obtained.